Characterizing fermented habanero pepper (Capsicum chinense L) - Alberta N.A. Aryee; James Owusu-Kwarteng; Zachary Senwo; Marikis N. Alvarez (Food Chemistry Advances, 2022)
Peppers are highly perishable vegetables, especially in tropical countries. Fermentation may serve as a bio-preservation approach to reduce spoilage, and valorization-enhancing process to improve sensory properties, safety, and nutritional value. The effects of salt concentrations on microbial diversity, sensory, metabolite and aroma profiles of naturally fermented habanero pepper was investigated by adding 5 - 25% (w/w) of salt to chopped habanero pepper and samples obtained on day 0, 7, 14, 30 and 50 for analyses. Lactic acid bacteria (LAB) increased from about 1.33 - 1.83 to 3.80 - 4.97 log CFU/mL during fermentation while pH decreased to 4.47 - 4.78. The presence of Enterobacteriaceae throughout the fermentation period reiterates the need to develop and implement starter cultures for fermenting habanero pepper. Untargeted metabolomics analysis revealed a total of 3206 metabolic features in the fermented peppers. Among these features, 121 were identified (confidence level 1), 1688 were putatively identified (confidence level 2), 1231 were predicted with a chemical formula (confidence level 3), and 166 were unidentified (confidence level 4). Clustering within the fermented groups was salt concentration dependent, with low salt groups (0% and 5%) distinguished from high salt groups (10%, 15%, 20% and 25%). Sensory evaluation showed similar scores for the various fermented peppers. A total of 18 volatile compounds including 10 alcohols, 3 esters, 2 ketones, and an acid were identified, and their content varied with salt concentration as explained by Principal Component Analysis.